2021
DOI: 10.3390/su13126760
|View full text |Cite
|
Sign up to set email alerts
|

Work from Home and the Use of ICT during the COVID-19 Pandemic in Indonesia and Its Impact on Cities in the Future

Abstract: The COVID-19 pandemic has resulted in restrictions on activities involving physical contact, such as working. Indonesia began to apply the system of work from home (WfH) to minimize the spread risk of COVID-19 in March 2020. This research is aimed at finding out the coverage of WfH, mapping changes of workplace, identifying the use of ICT to support WfH, and analyzing the concept of workplace and work systems in future cities. The method used in this research is qualitative and quantitative. A questionnaire (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 27 publications
0
39
0
2
Order By: Relevance
“…Considering the WFH teaching model and the use of ICT tools, a study has shown that the application of ICT technologies balances out one's private and professional life, which has already been discussed [74]. The implementation of ICT is necessary and fundamental to the functioning of WFH during the pandemic [75].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the WFH teaching model and the use of ICT tools, a study has shown that the application of ICT technologies balances out one's private and professional life, which has already been discussed [74]. The implementation of ICT is necessary and fundamental to the functioning of WFH during the pandemic [75].…”
Section: Discussionmentioning
confidence: 99%
“…With the policy of working from home, supported by making use of ICT, the mobility of people from home to workplace can be reduced. This leads to positive impacts on traffic, air pollution, and the need for office space [1].…”
Section: Aspects Of Ict-based Application and Smart Citymentioning
confidence: 99%
“…One of the implications of this is the implementation of working from home (WFH), caused by the need for social distancing. Working from home leads to other changes in life, such as the methods of working, fulfilling daily needs, interacting with other people, and making use of spaces [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is needed to determine which issues should be prioritized for consideration and planning. In the period of working from home policy in Indonesia, many studies have been conducted to try to capture emerging phenomena from various perspectives, for example, information technology [13], health [14], gender [15], government policy [16], psychology [17], economy [18] education [19], and various perspectives and methods. However, research that analyzes the elements of work from home and determines the priorities of these elements has not been carried out.…”
Section: Introductionmentioning
confidence: 99%